Detecção de patógenos em ponta de cateter venoso central por reação em cadeia da polimerase - Maristela Oliveira Lara (2018)
Healthcare-associated infections (HAIs) are worrying adverse events in public health. They are an important cause of morbidity and mortality in intensive care units. Invasive devices such as the central venous catheter (CVC) favors a type of HAIs, the bloodstream infection. This event is commonly diagnosed by blood culture and/or culture of the catheter tip, however, the response time of these tests or their results not always contribute to the appropriate treatment. Advances in biotechnology provide tools capable of contributing to diagnoses of infection. The aim of the present thesis was to detect potentially pathogenic bacteria at the tip of a central venous catheter through polymerase chain reaction (PCR). Subjects were treated with DNA extraction and molecular tracing in CVC. It is a cross-sectional molecular study. Laboratory tests comparing DNA extraction methods were performed with the Staphylococcus aureus bacterium for subsequent application to catheters collected from patients. Over a period of 6 months, in an Adult Intensive Care Unit of a philanthropic and training hospital, (n=34) catheters were removed from patients under suspicion of bloodstream infection. All the thirty-four catheters were subjected to DNA extraction from the biological material contained in their wall and inside their lumens. The bacteria were identified by PCR using a standard set of reagents and temperatures. The results found in the analysis by molecular biology were compared with the results of the cultures of these patients, performed by the hospital. Collection of patients' data was also carried out: sex, age, use of other invasive devices, CVC insertion location and period of catheters use; and presence of phlogistic signs in the insertion site of the device. Statistical tests were used with the help of the Stata software, version 15. The prevalence of bacteria in CVCs was: Staphylococcus aureaus (50%), Enterococcus faecalis (41,2%), Klebsiella pneumoniae (32,4%), Pseudomonas aeruginosa (20,6%), Acinetobacter baumannii (38,2%) and Escherichia coli (2,9%). All blood cultures performed had no bacteria as a result of the examination. Catheter-tip culture revealed microorganisms in 21 (61.8%) devices, whereas PCR showed positivity in 31 (91.2%). The most commonly detected pathogens are usually found in the environment and in the microbioma of the skin and they are possibly transmitted to patients by the hands of health professionals. These findings are relevant when programming CVC-related bloodstream infection prevention measures. The genomic material extraction method, primers panel and amplification protocol of this study identified the major pathogens prevalent in bloodstream infections. In this way, molecular identification of bacteria may assist in the detection of bloodstream infection and decision-making regarding the choice of the best therapy.